Preparation method of mesoporous silica nano material based on lipoprotein compound electrostatic adsorption and application of antibacterial adjuvant
Through the mesoporous silica lipoprotein complex drug-loading system based on electrostatic action, the problems of high antibiotic resistance and HAMLET/BAMLET preparation cost are solved, and the effect of restoring MRSA sensitivity and slowly releasing antioxidant drugs is achieved. New antibacterial adjuvant strategies were developed.
Patent Information
- Application Number
- CN202411333264.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
AI Technical Summary
Antibiotic abuse leads to bacterial resistance problems, traditional antibiotic drug development stagnates, lack of effective strategies to deal with the growing threat of antibiotic resistance, and the traditional preparation method of HAMLET/BAMLET consumes a lot of manpower and material resources, hindering its practical application.
Using a mesoporous silica lipoprotein complex drug-loading system based on electrostatic-stabilizing action, lipoprotein encapsulation media was prepared by a combination of aminating mesoporous silica nanoparticles and bovine α-whey albumin and oleic acid. Porous silica-loaded antioxidant drug composites are used as antibacterial adjuvant with aminoglycoside antibiotics to restore the sensitivity of MRSA.
The sensitivity of MRSA to traditional antibiotics was achieved, reducing the preparation cost and time, and the loaded antioxidant drugs were slowly released, removing free radicals from infected areas, significantly improving the therapeutic effect.
Smart Images

Figure CN119185250A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of antibacterial technology of nano drug delivery system, and specifically relates to a preparation method of mesoporous silica nanomaterial based on electrostatic adsorption of lipoprotein complex and application of antibacterial adjuvant. Background Art
[0002] At present, antibiotics are effective drugs for treating clinical bacterial infections, but the abuse of antibiotics leads to bacterial resistance to antibiotics, affecting the therapeutic effects of drugs and even leading to the dilemma of no drugs available.
[0003] The lipoprotein complex HAMLET / BAMLET, discovered in 1995, is composed of human / bovine α-lactalbumin and oleic acid. It was originally found to kill cancer cells for tumor treatment. Studies have shown that in addition to anti-tumor effects, HAMLET / BAMLET can also kill bacteria through a mechanism related to cell apoptosis. It also has the potential to be an antibiotic enhancer, restoring the sensitivity of Streptococcus pneumoniae to β-lactam antibiotics, but there are few reports on studies on drug-resistant bacteria. HAMLET / BAMLET is usually prepared by column exchange or dialysis.
[0004] Mesoporous silica (MSN) has a high specific surface area, and its particle size and morphology are controllable, and its surface is easily functionalized. As an ideal nano-delivery platform, MSN can effectively load small molecules, proteins and other drugs through electrostatic adsorption or chemical bonding. The particle size of MSN is a key factor affecting the composition and structure of protein adsorbed on its surface. In biological fluids, different serum protein coronas are formed on the surface of silica nanoparticles of different particle sizes, and the formed protein coronas may directly affect the fate of nanoparticles in the organism.
[0005] The development of new antibiotic drugs against resistant bacteria has stagnated and is insufficient to address the growing threat of antibiotic resistance.
[0006] The MIC of HAMELT / BAMLET as an antibacterial agent is within mg / mL. The traditional preparation method consumes a lot of manpower and material resources, which hinders its practical application. Therefore, the development of nano-delivery carriers greatly reduces the preparation cost and time by electrostatically adsorbing lipoprotein complexes. However, the selection and preparation of nano-delivery carriers of appropriate size are not considered, which will greatly affect the effect of lipoprotein complexes.
[0007] Therefore, there is an urgent need to restore the sensitivity of resistant bacteria to traditional antibiotics and provide new strategies to alleviate the antibiotic resistance crisis. Summary of the invention
[0008] In view of the shortcomings of the existing problems, the purpose of the present invention is to provide a mesoporous silica lipoprotein complex drug delivery system and antibacterial adjuvant application based on electrostatic stabilization.
[0009] The technical solution adopted by the present invention to solve the technical problem is:
[0010] In a first aspect, the present invention claims a method for preparing a mesoporous silica lipoprotein complex drug delivery system based on electrostatic stabilization, the method comprising the following steps:
[0011] In the first step, amino-modified mesoporous silica nanoparticles are prepared;
[0012] The second step is to evenly disperse the antioxidant drug in ethanol, add the amino-modified mesoporous silica nanoparticles, stir at room temperature, and obtain the drug-loaded mesoporous silica nanoparticles after drying;
[0013] The third step is to uniformly disperse the drug-loaded mesoporous silica nanoparticles in a phosphate buffer solution by ultrasonication, add bovine α-lactalbumin (BLA) thereto, and incubate with shaking;
[0014] The fourth step is to add oleic acid (OA) after the incubation is completed, and then incubate the mixture statically. After the reaction, the mixture is dried to obtain a lipoprotein-encapsulated mesoporous silica-loaded antioxidant drug composite material.
[0015] In a specific embodiment, in the first step, the amino-modified mesoporous silica is purchased commercially or prepared by itself.
[0016] In a more specific embodiment, the present invention provides a method for preparing amino-modified mesoporous silica, the preparation method is as follows:
[0017] (1) Weighing hexadecyltrimethylammonium bromide (CTAB) and alkali in deionized water at 80-95° C. for reaction for 0.1-1 h, stirring continuously during the reaction; then adding tetraethyl orthosilicate (TEOS) and continuing the reaction for 1-2 h, and collecting by centrifugation;
[0018] (2) calcining the dried product obtained in step (1) in a muffle furnace at 550±50° C. for 4-8 h, preferably 6 h, to remove hexadecyltrimethylammonium bromide (CTAB);
[0019] (3) dispersing the product collected in step (2) in ethanol, adding 3-aminopropyltriethoxysilane (APTES), and condensing and refluxing at 78±5° C. for 12-24 h;
[0020] (4) The product in step (3) is collected by centrifugation, washed, and dried to obtain MSN-NH2.
[0021] In a more specific embodiment, in the step (1), the base is triethanolamine (TEA) or NaOH, etc. By changing the amount of TEA or NaOH added, mesoporous silica nanocarriers of different sizes can be prepared. For example, 71.2 μL TEA is added in step (1), and a mesoporous silica nanocarrier of 25 nm ± 10 nm can be obtained after a subsequent treatment step; 50 μL TEA is added in step (1), and a mesoporous silica nanocarrier of 50 nm ± 5 nm can be obtained after a subsequent treatment step. In step (1), 0.2 g CTAB and 700 μL NaOH (2.0 M) are first added, and reacted at 80 ° C in 96 ml deionized water for 0.5 h, with continuous stirring during the reaction; then 1.5 mL tetraethyl orthosilicate (TEOS) is added dropwise and the reaction is continued for 1 h, and the mixture is collected by centrifugation, and 100 nm ± 10 nm can be obtained after a subsequent treatment step.
[0022] In a specific embodiment, in step (3), the mass volume ratio of MSN to ethanol is 100±30 mg:20±5 mL. In a specific embodiment, the antioxidant drug in the second step is curcumin.
[0023] Preferably, the method of the second step is as follows:
[0024] (1) The hydrophobic antioxidant drug curcumin (Cur) is dispersed in ethanol, and MSN-NH2 is added at a mass ratio of 2:1 to 1:1 with Cur, the reaction temperature is 25±5°C, and the reaction time is at least 24h;
[0025] (2) The reaction product was collected by centrifugation, washed with deionized water, and dried to obtain curcumin-loaded mesoporous silica nanoparticles (MSN-NH2 / Cur).
[0026] In a specific embodiment, the mass ratio of MSN-NH2 to Cur is 1:1.
[0027] In a specific embodiment, in the fourth step, the molar ratio of oleic acid to α-lactalbumin is 30-50:1, preferably 40:1, and the reaction conditions are: reaction temperature 45±5°C, reaction time 15±5min; the precipitate is collected by ultracentrifugation and freeze-dried to obtain a solid material (BMSN / Cur).
[0028] In a second aspect, the present invention protects a lipoprotein-encapsulated mesoporous silica-loaded antioxidant drug composite material (also known as lipoprotein composite nanoparticles) prepared by the above method.
[0029] In a third aspect, the present invention protects the use of the above-mentioned lipoprotein-encapsulated mesoporous silica-loaded antioxidant drug composite material in the preparation of antibiotic adjuvants.
[0030] In a specific embodiment, the antibiotic adjuvant further contains a pharmaceutically acceptable excipient.
[0031] The active ingredient as an antibiotic adjuvant combined with aminoglycoside antibiotics can restore MRSA's sensitivity to traditional antibiotics. The antioxidant drugs loaded in the pores are slowly released to remove free radicals generated at the infection site, which is beneficial to the treatment and recovery of the bacterial infection site.
[0032] Beneficial Effects
[0033] The lipoprotein-wrapped mesoporous silica-loaded antioxidant drug composite material nanoparticles obtained by the present invention can be used as active ingredients of antibiotic adjuvants to restore the sensitivity of MRSA to aminoglycoside antibiotics.
[0034] The lipoprotein-wrapped mesoporous silica loaded antioxidant drug composite material nanoparticles of the present invention have a simple preparation method, low toxicity to normal cells, and good biocompatibility. The loaded antioxidant drug can remove free radicals and accelerate the recovery of the wound infection site. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of the reaction principle of Examples 1, 2, and 3 of the present invention.
[0036] Figure 2 The morphological characterization of the nanomaterials obtained in Examples 1, 2, and 3 of the present invention. Transmission electron microscope images and scanning electron microscope images of 25BMSN / Cur, 50BMSN / Cur, and 100BMSN / Cur (AC). The inset shows the size distribution of three different particle sizes of BMSN / Cur.
[0037] Figure 3 The physical and chemical characterization of the nanoparticles obtained in Examples 1, 2, and 3 of the present invention; wherein, Figure 3 A-3C is the infrared spectra of three mesoporous silica composite nanoparticles with different particle sizes; Figure 3 D is the SDS-PAGE gel analysis of the samples using Coomassie Brilliant Blue staining; Figure 3 E is the UV-visible spectrum; Figure 3 F is the Zeta potential diagram of the nanoparticles; Figure 3 G is the Cur release curve of BMSN / DTX at pH 7.4.
[0038] Figure 4 It is the free radical scavenging rate of the nanoparticles obtained in Examples 1, 2 and 3 of the present invention.
[0039] Figure 5 The MIC test results of the single and combined anti-MRSA agents in Example 2 of the present invention are shown in FIG. Figure 5 A is the inhibition rate of two aminoglycoside antibiotics against MRSA; Figure 5 B is the antibacterial rate of MRSA by three lipoprotein composite nanoparticles with different particle sizes; Figure 5 C-5E is the survival rate of MRSA after the three different sized lipoprotein composite nanoparticles were combined with gentamicin; Figure 5 F-5H is the survival rate of MRSA after three different particle size composite nanoparticles were combined with kanamycin.
[0040] Figure 6 The evaluation of cytotoxicity and cell migration ability of Example 2 of the present invention when used alone or in combination; wherein, Figure 6 A-6C is the cytotoxicity of lipoprotein complex nanoparticles alone and in combination to 3T3 cells; Figure 6 D-6F is a lipoprotein complex nanoparticle that is toxic to HSF cells when used alone or in combination; Figure 6 G shows the effects of protein composite nanoparticles alone and in combination on HSF cell migration.
[0041] Figure 7 This is a scanning electron microscope image of the effects of Example 2 of the present invention used alone and in combination on bacterial morphology.
[0042] Figure 8 The therapeutic effects of Example 2 of the present invention alone and in combination on bacterial infection on the skin surface in vitro; wherein, Figure 8 A is the image of infected skin and bacterial colony plating after lipoprotein composite nanoparticles alone and in combination; Figure 8 B is the colony count results after lipoprotein complex nanoparticles alone and combined treatment. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below with reference to the examples. The reagents or instruments used without indicating the manufacturer are regarded as conventional products that can be purchased on the market.
[0044] Abbreviations: CTAB, cetyltrimethylammonium bromide; TEA, triethanolamine; TEOS, tetraethoxysilane; APTES, 3-aminopropyltriethoxysilane; Cur, curcumin; BLA, bovine alpha lactalbumin; oleic acid, OA.
[0045] Example 1: Synthesis of 25BMSN / Cur
[0046] 2g CTAB and 71.2μL TEA were reacted in 20ml deionized water at 95℃ for 1h, with continuous stirring during the reaction; then 1.5mL TEOS was added dropwise at 0.25ml / min, and the reaction was continued for 1h. The reaction product was collected by centrifugation at 10000rpm for 10min, washed with ethanol 3 times, dried and collected, and calcined at 550℃ in a muffle furnace for 6h to obtain 25nm MSN. 100mg 25MSN was dispersed in 20ml ethanol, 150μL APTES was added, and after condensation and reflux at 78℃ for 12h, the reaction product was collected by centrifugation at 10000rpm for 10min, washed with ethanol and deionized water 3 times respectively, and dried to obtain 25MSN-NH2. Disperse 10mg 25MSN-NH2 in 2.5ml ethanol, add 10mg Cur, react at 600rpm at room temperature for 24h, collect the reaction product by centrifugation at 10000rpm for 10min, wash with deionized water 3 times, dry and collect to obtain 25MSN-NH2 / Cur. Disperse 5mg 25MSN-NH2 / Cur in PBS (pH=8), add 10mg BLA, mediate for 30s, react at room temperature for 30min, add OA at a ratio of OA to BLA of 40:1, water bath at 45℃ for 15min, collect the product by centrifugation at 10000rpm for 10min, and freeze-dry to obtain 25BMSN / Cur.
[0047] Example 2: Synthesis of 50BMSN / Cur
[0048] 2g CTAB and 50μL TEA were reacted in 20ml deionized water at 95℃ for 1h, with continuous stirring during the reaction; then 1.5mL TEOS was added dropwise at 0.25ml / min, and the reaction was continued for 1h. The reaction product was collected by centrifugation at 10000rpm for 10min, washed with ethanol 3 times, dried and collected, and calcined at 550℃ in a muffle furnace for 6h to obtain 50nm MSN. 100mg 50MSN was dispersed in 20ml ethanol, 150μL APTES was added, and after condensation and reflux at 78℃ for 12h, the reaction product was collected by centrifugation at 10000rpm for 10min, washed with ethanol and deionized water 3 times respectively, and dried to obtain 50MSN-NH2. Disperse 10mg 50MSN-NH2 in 2.5ml ethanol, add 10mg Cur, react at 600rpm at room temperature for 24h, collect the reaction product by centrifugation at 10000rpm for 10min, wash 3 times with deionized water, dry and collect to obtain 50MSN-NH2 / Cur. Disperse 5mg 50MSN-NH2 / Cur in PBS (pH=8), add 10mg BLA, mediate for 30s, react at room temperature for 30min, add OA at a ratio of OA to BLA of 40:1, water bath at 45℃ for 15min, collect the product by centrifugation at 10000rpm for 10min, and freeze-dry to obtain 50BMSN / Cur.
[0049] Example 3: Synthesis of 100BMSN / Cur
[0050] 0.2g CTAB and 700μL NaOH (2.0M) were reacted in 96ml deionized water at 80℃ for 0.5h, with continuous stirring during the reaction; then 1.5mL TEOS was added dropwise at 0.25ml / min, and the reaction was continued for 2h. The reaction product was collected by centrifugation at 10000rpm for 10min, washed with ethanol 3 times, dried and collected, and calcined at 550℃ in a muffle furnace for 6h to obtain 100nm MSN. 100mg100MSN was dispersed in 20ml ethanol, 150μL APTES was added, and after condensation and reflux at 78℃ for 12h, the reaction product was collected by centrifugation at 10000rpm for 10min, washed with ethanol and deionized water 3 times respectively, and dried to obtain 100MSN-NH2. Disperse 10mg100MSN-NH2 in 2.5ml ethanol, add 10mg Cur, react at 600rpm at room temperature for 24h, collect the reaction product by centrifugation at 10000rpm for 10min, wash with deionized water 3 times, dry and collect to obtain 100MSN-NH2 / Cur. Disperse 5mg100MSN-NH2 / Cur in PBS (pH=8), add 10mg BLA, mediate for 30s, react at room temperature for 30min, add OA at a ratio of OA to BLA of 40:1, water bath at 45℃ for 15min, collect the product by centrifugation at 10000rpm for 10min, and freeze-dry to obtain 100BMSN / Cur.
[0051] Performance Test:
[0052] 1. The BMSN / Cur of different particle sizes prepared in Examples 1, 2, and 3 were subjected to a number of tests, the results of which included: transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared spectrometry (FTIR), UV-visible spectrometry, SDS-PAGE gel image, Zeta potential, and in vitro release curve.
[0053] The following are the results of testing the BMSN / Cur prepared in Examples 1, 2, and 3.
[0054] Figure 2 The TEM and SEM images of 25BMSN / Cur, 50BMSN / Cur, and 100BMSN / Cur show the size distribution of the three nanoparticles. It can be seen that the silica composite material is obviously spherical, and the nanoparticles are monodispersed.
[0055] Figure 3The physicochemical characterization of the nanoparticles prepared in Examples 1, 2, and 3 of the present invention. The sample spectra were recorded using Fourier transform infrared spectroscopy (FT-IR) and ultraviolet spectrophotometers. After the surfactant was removed, no characteristic CH peak appeared in the MSN within the wavelength range of 3000-2800cm-1, indicating that the surfactant CTAB had been completely removed. For MSN-NH2, the peaks at 802, 940, 1097, and 1621cm-1 were attributed to Si-O symmetric stretching, Si-OH bending vibration, Si-O-Si asymmetric stretching vibration, and NH bending vibration, respectively. The characteristic peaks of curcumin appeared in both MSN-NH2 and BMSN / Cur, indicating that curcumin was effectively encapsulated. In addition, in the ultraviolet spectrum, the three BMSNs showed characteristic peaks belonging to proteins at 280-300nm. By SDS-PAGE analysis, the band at 14.0kDa of the material after protein coating was similar to the BLA band. All three particle sizes of BMSN / Cur have the ability to slowly release Cur. The change in zeta potential also indicates the success of each modification and protein coating step.
[0056] 2. Experimental methods: We evaluated the antioxidant capacity of nanoparticles by free radical scavenging experiments.
[0057] The ability of curcumin loaded in MSN pores to scavenge free radicals increases with the increase of concentration. Figure 4 As shown in the figure, at the same concentration, the three different particle sizes of BMSN / Cur all showed similar antioxidant capacity as curcumin, indicating that the activity of curcumin was not affected after loading. Therefore, the synthesized BMSN / Cur has the ability to scavenge reactive oxygen free radicals, which is beneficial to wound repair.
[0058] 3. Test method: Combined antimicrobial test-checkerboard method.
[0059] Samples of different concentrations were dissolved in LB liquid medium to evaluate the MIC of materials with different particle sizes and antibiotics alone or in combination. The final concentration of MRSA was 5 × 10 5 CFU / mL, 100 μL of sample solution was mixed with 100 μL of prepared bacterial suspension in a 96-well plate. Each sample was prepared in parallel three times. Cultured at 37°C for 18 hours. LB medium alone and bacterial suspension without sample were used as negative and positive controls, respectively. The solution containing only sample was used as blank control. The absorbance of the culture solution was measured at a wavelength of 600 nm using a multifunctional plate reader. The lowest concentration with an inhibition rate of more than 80% was defined as MIC. Figure 5 It can be seen that the combination therapy has a synergistic antibacterial effect compared with the single therapy. Among them, the nanoparticles prepared in Example 2 have a stronger synergistic effect, reducing the MIC of gentamicin by 16 times.
[0060] 4. Experimental methods: cytotoxicity assessment.
[0061] The cytotoxicity of the nanoparticles prepared in Example 2 of the present invention on mouse fibroblasts (3T3) and human skin fibroblasts (HSF) was evaluated, and their effect on the migration ability of HSF cells was evaluated. Figure 6 As shown, the combined therapy has low cytotoxicity within the applied concentration range and exhibits good biocompatibility; at the same time, the combined therapy has the effect of promoting HSF cell migration.
[0062] 5. Experimental method: Observation of bacterial morphology using scanning electron microscope.
[0063] To evaluate the interaction between the nanoparticles prepared in Example 2 of the present invention and the bacteria, the morphology of the bacteria after different sample treatments was observed using a scanning electron microscope (SEM). Figure 7 As shown in the figure, when antibiotics are used alone, the morphological structure of MRSA does not change significantly. Nanoparticles can be adsorbed on the surface of bacteria, and the surface of the bacteria in contact becomes concave. In the combined therapy, the surface of MRSA becomes concave and wrinkled, and the contents leak out, which has better antibacterial activity.
[0064] 6. Experimental method: in vitro skin infection experiment.
[0065] Fresh pig skin was used as the skin model for this experiment. The skin was cleaned with saline to remove surface stains, and then the pig skin was cut into 1.5cm×1.5cm explants. It was cleaned with 75% medical alcohol to remove bacteria and then sterilized under ultraviolet light. On the surface of the sterilized pig skin, a wound with a diameter of 10mm was cut with a punch. The explant was placed on a 12-well plate containing 1.5mL saline agar (0.9% NaCl, 0.5% agar) to simulate human skin conditions. 50μL of MRSA suspension (106CFU / mL) cultured in LB was inoculated into the wound and cultured at 37℃ for 2h to allow bacteria to establish infection. Subsequently, single and combined treatments were performed on the infected site of the wound and cultured at 37℃ for another 24h. Then, 1mL PBS was added to the infected site, and the wound site was rubbed with a sterile inoculation loop to collect bacterial cells. The antibacterial effect was evaluated by the dilution spread plate method and colony count method. The experiment was divided into four groups, and each group was repeated three times (n=3).
[0066] Figure 8 The therapeutic effect of the in vitro skin antibacterial experiment using the combined therapy in Example 2 of the present invention. The results of the coating plate after 24 hours of treatment showed that the antibacterial effect of the combined treatment group was significant compared with the single treatment. Subsequently, the collected bacterial solution was serially diluted at a certain multiple, and the bacteria were counted again by the coating plate method. The results showed that the number of bacterial colonies in the combined treatment group was reduced by about one order of magnitude compared with the other sample treatment groups.
[0067] The protection content of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention and are protected by the attached claims.
Claims
1. A method for preparing a mesoporous silica lipoprotein complex drug delivery system based on electrostatic stabilization, the method comprising the following steps: In the first step, amino-modified mesoporous silica nanoparticles are prepared; The second step is to evenly disperse the antioxidant drug in ethanol, add the amino-modified mesoporous silica nanoparticles, stir at room temperature, and obtain the drug-loaded mesoporous silica nanoparticles after drying; The third step is to uniformly disperse the drug-loaded mesoporous silica nanoparticles in a phosphate buffer solution by ultrasonication, add bovine α-lactalbumin thereto, and incubate with shaking; The fourth step is to add oleic acid after the incubation is completed, incubate statically, and dry after the reaction to obtain a lipoprotein-encapsulated mesoporous silica-loaded antioxidant drug composite material.
2. The method according to claim 1, characterized in that The amino-modified mesoporous silica is purchased commercially or prepared by itself.
3. The method according to claim 2, characterized in that The preparation method of the amino mesoporous silica is as follows: (1) Weighing hexadecyltrimethylammonium bromide and alkali, reacting in deionized water at 80-95° C. for 0.5-1 h, stirring continuously during the reaction; then adding tetraethyl orthosilicate, continuing the reaction for 1-2 h, and collecting by centrifugation; (2) calcining the dried product obtained in step (1) at 550±50° C. for 4-8 h, preferably 6 h, and collecting the product mesoporous silica; (3) dispersing the product collected in step (2) in ethanol, adding 3-aminopropyltriethoxysilane, and condensing and reflux at 78±5° C. for 12-24 h; (4) The product in step (3) is collected by centrifugation, washed, and dried to obtain amino-modified mesoporous silica.
4. The method according to claim 3, characterized in that In the step (1), the base is triethanolamine or NaOH; Preferably, in step (3), the mass volume ratio of mesoporous silica to ethanol is 100±30 mg:20±5 mL.
5. The method according to claim 1, characterized in that The antioxidant drug in the second step is curcumin.
6. The method according to claim 5, characterized in that The method of the second step is as follows: (1) Dispersing curcumin Cur in ethanol, adding aminated mesoporous silica in a mass ratio of 2:1 to 1:1, preferably 1:1, with a reaction temperature of 25±5°C and a reaction time of at least 24h; (2) The reaction product was collected by centrifugation, washed with deionized water, and dried to obtain curcumin-loaded mesoporous silica nanoparticles MSN-NH2 / Cur.
7. The method according to claim 5, characterized in that The method of the fourth step is as follows: the molar ratio of oleic acid to α-lactalbumin is 30-50:1, preferably 40:1, and the reaction conditions are: reaction temperature 45±5°C, reaction time 15±5min; The precipitate was collected by ultracentrifugation and then freeze-dried to obtain a solid material.
8. A composite material of lipoprotein-encapsulated mesoporous silica loaded with antioxidant drugs prepared by the method according to any one of claims 1 to 7.
9. Use of the lipoprotein-encapsulated mesoporous silica-loaded antioxidant drug composite material according to claim 8 in the preparation of antibiotic adjuvants.
10. The use according to claim 9, characterized in that: The antibiotic adjuvant further contains pharmaceutically acceptable excipients.
